2023
DOI: 10.1021/acs.energyfuels.3c00313
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Recovery of Valuable Metals from Lithium-Ion Battery Cathodes Using Phytic Acid-Based Deep Eutectic Solvents at a Mild Temperature

Abstract: Recycling of waste lithium-ion batteries (LIBs) requires metal leaching from the LIB cathode; however, the metal-leaching process is too challenging to be efficient, green, and mild simultaneously. Moreover, the leaching efficiency at mild conditions by green solvents is not high and needs to be improved urgently. Here, deep eutectic solvents (DESs) composed of poly(ethylene glycol) 200 (PEG) and phytic acid (PHA) are designed to leach Co from LIB cathodes with an ultrahigh metalleaching efficiency of 0.987 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…PEG and PHA were mixed with the mole ratio of 1:1 to obtain DESs at 60 °C until the appearance of the liquid state, which was similar to the methods as previously reported. ,, Magnetic adsorbents could be then synthesized by mixing DESs, Fe 3 O 4 , and LCO with a mass ratio of 1:5:0.1 at 100 °C for 24 h. A previous report suggested that PEG:PHA could dissolve LCO with high efficiency at a mild temperature; however, the leaching efficiency became lower as a result of the formation of the solid product when the temperature was not lower than 100 °C. The possible mechanism for the formation of magnetic adsorbent from DESs, Fe 3 O 4 , and LCO was the redox reaction between LCO and DESs, while Fe 3 O 4 plays the role of possessing magnetism.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…PEG and PHA were mixed with the mole ratio of 1:1 to obtain DESs at 60 °C until the appearance of the liquid state, which was similar to the methods as previously reported. ,, Magnetic adsorbents could be then synthesized by mixing DESs, Fe 3 O 4 , and LCO with a mass ratio of 1:5:0.1 at 100 °C for 24 h. A previous report suggested that PEG:PHA could dissolve LCO with high efficiency at a mild temperature; however, the leaching efficiency became lower as a result of the formation of the solid product when the temperature was not lower than 100 °C. The possible mechanism for the formation of magnetic adsorbent from DESs, Fe 3 O 4 , and LCO was the redox reaction between LCO and DESs, while Fe 3 O 4 plays the role of possessing magnetism.…”
Section: Methodsmentioning
confidence: 89%
“…Some DESs are reported to be unstable , and toxic; instead, it could be overcome by applying the high tunability of DESs. Therefore, DESs have been applied in many fields, , including acting as green solvents for lithium-ion battery (LIB) dissolution and recovery. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, microbial leaching is also a novel method for recovering cathode active substances, which has the benefits of low cost, reduced pollution, and high recyclability, and has become an important development direction of the recycling technology for valuable metals from SLIBs. , However, conventional biotechnology faces issues of a slow leaching rate, long leaching time, and difficulties in the selection and cultivation of microbial strains. , Ultrasound-assisted technology can increase the metal extraction efficiency of biolixiviation by increasing the yield of metabolites and enhancing mixing in the microscale . Therefore, ultrasound-assisted microbial leaching is also a promising alternative for the green recovery of valuable metals from SLIBs.…”
Section: Discussionmentioning
confidence: 99%
“…107,108 However, conventional biotechnology faces issues of a slow leaching rate, long leaching time, and difficulties in the selection and cultivation of microbial strains. 109,110 Ultrasound-assisted technology can increase the metal extraction efficiency of biolixiviation by increasing the yield of metabolites and enhancing mixing in the microscale. 111 Therefore, ultrasound-assisted microbial leaching is also a promising alternative for the green recovery of valuable metals from SLIBs.…”
Section: Valuable Metals Recovery From Cathode Materialsmentioning
confidence: 99%